THE EFFECTIVENESS OF ORGANIC AGRICULTURE IN SUPPORTING A SUSTAINABLE FOOD SYSTEM: A REVIEW OF THE LATEST LITERATURE - Suslinawati; Caroline Caroline; Afwan Sila (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the effectiveness of organic agriculture in supporting sustainable food systems through a review of the latest literature. The results of the study show that organic agriculture can contribute significantly to food sustainability by prioritising the efficient and regenerative use of natural resources and reducing the use of synthetic chemical inputs. In addition, organic agriculture supports biodiversity, maintains soil fertility, and minimises environmental pollution. However, the implementation and scale of organic agriculture still faces various challenges, including high production costs and lower yields. Government support through enabling policies, subsidy programmes, and investment in training and education is needed to overcome these challenges. With the right support, organic farming has great potential to play a key role in a sustainable food system, providing comprehensive environmental, social, and health benefits.